Isolation of acephate-degrading bacteria and phytoremediation–microbial remediation from soil for the project of water diversion from the Yangtze River to Chaohu Lake - Wang, Huili; Chang, Jielun; Pan, Chang; Jiang, Dongsheng; Wang, Yemei; Yin, Qin; Chen, Xi; Liao, Xi; Li, Manman; Zhang, Xiaoke (Frontiers in Microbiology, 2025)
IntroductionEfficient and safe governance of soil contaminated with organophosphate pesticides is of crucial significance for the protection of the ecosystem. This study focuses on soils from typical riparian zones along the project of water diversion from the Yangtze River to Chaohu Lake, aiming to screen acephate-degrading microorganisms and to systematically evaluate their degradation efficiency.MethodsAcephate-degrading bacteria were isolated from soil via enrichment culture with acephate as the sole carbon source, and their degradation efficiency was subsequently evaluated. Subsequently, a pot experiment was designed to investigate the efficiency of the combined remediation of soil acephate through the synergistic action of the isolated bacteria and plants.ResultsFive acephate-degrading strains were isolated and identified via 16S rDNA sequencing as Enterobacter cloacae, Enterobacter hormaechei, Bacillus badius, Sphingobacterium spiritivorum, and Serratia nematodiphila. Although all strains degraded acephate, their efficiencies differed significantly. Except for the 50 mg L−1 acephate condition with added glucose, B. badius consistently exhibited higher degradation efficiency across all tested conditions. Furthermore, increasing acephate concentration in the culture medium from 10 to 50 mg L−1 reduced degradation efficiency across strains. However, adding 0.1 g L−1 glucose enhanced degradation rates for all strains, with B. badius achieving the highest degradation efficiency (76.17% at 10 mg L−1 acephate). For combined experiments, we paired B. badius (with superior in vitro degradation performance) with Persicaria hydropiper, and S. spiritivorum with Carex dimorpholepis. At both 200 μg kg−1 and 1,000 μg kg−1 soil acephate concentrations, combined remediation efficiencies exceeded those of microbes or plants alone. The combination of B. badius and P. hydropiper achieved the highest removal rate of 91.27% at the 1,000 μg kg−1 acephate concentration.ConclusionThese findings significantly enrich the repository of acephate-degrading bacteria and demonstrate that combined remediation with B. badius and P. hydropiper is an effective strategy for the bioremediation of acephate-contaminated soils within the project of water diversion from the Yangtze River to Chaohu Lake.